Effect of enhancing biofertilizer containing K solubilizer on patchouli growth - Mohd Syahir, Mohamad Nasir (2009)
Biofertilizers are products containing living cells of different types of microorganisms, which have an ability to convert nutritionally important elements from unavailable to available form through biological processes. However, the application of biofertilizer in practice, somehow, has not achieved constant effects on the plants growth. The objectives of this paper are to study the effect of biofertilizer enhance with K solubilizer inoculums on plants growth and making a comparison on physical appearances of patchouli growth between modified biofertilizer, biofertilizer, organic fertilizer and chemical fertilizer. In order to achieve the objectives, this study is devided into two part which are the K solubilizer bacteria cultivation and pots experiment. The cultivation of K solubilizer bacteria was carried out on 72 hour of fermentation at 28°C and at the speed of 200 rpm. The K solubilizer bacteria growth curve and their glucose consumption were determined at 3 hour interval for the first 24 hour and 6 hour interval for the next 48 hour. The result showed that K solubilizer bacteria is in active phase in its first 40 hour of cultivation. The pots experiment were carried out by eight treatments with duplication. The modifications of biofertilizer were coded as BF5 for 5% of inoculums, BFlO for 10% of inoculums, BF15 for 15% of inoculums and BF20 for 20% of inoculums. Another four treatments were set up as comparison including chemical fertilizer, sterilized organic fertilizer, biofertilizer and no fertilizer (control). Data were taken after 6 weeks of seedling. The result showed that after 6 weeks of seedling, the enhanced biofertilizer are capable of showing outcome as best as chemical fertilizer in terms of physical appearences and potassium content in the soil. Therefore, the application of the enhance biofertilizer containing beneficial microbes showed a promoting effect on the growth of plant and improvement of soil properties.